Images of Educational Leadership: How Principals Make Sense of Democracy and Social Justice in Two Distinct Policy Contexts. (October 2021) - Trujillo, Tina; Møller, Jorunn; Jensen, Ruth; Kissell, René Espinoza; Larsen, Eivind
Purpose: This article investigates how school leaders make sense of social justice and democracy in their practice in two settings, a high-stakes testing and accountability context, the San Francisco Bay Area, California, and a low-stakes testing and accountability context, Norway. It demonstrates how leaders view relationships among education, democracy, and social justice, when located in a neoliberal democracy with a minimalist welfare state or in a social democracy with a robust welfare state.Design and Evidence: Through a comparative design, we analyze qualitative data from two international principal exchanges designed to capture outsiders' impressions of schools in each context. Participants included alumni from an American and a Norwegian university's principal preparation programs. Through preobservation and postobservation interviews and focus groups, we explore observations by practitioners, who acted as coconstructors in the research.Findings and Implications: The article presents three findings: (1) While principals in both systems conceptualized equity similarly, their conceptions of democracy were aligned with the type of democracy in which they were embedded; (2) Schools' norms, climate, structures, and leadership, as well as students' daily lives, reflected the values implicit in their respective political contexts; (3) Principals perceived elements of their macro- and micro-level settings to enable or constrain their ability to craft democratic, socially just schools. These findings help scholars move beyond discourse about the need for leaders to advocate for equity, to deeper understandings about conditions that shape democratic schools, such as values about collectivism, welfarism, and the common good—tenets of a socially just civic society.